Aging in epitaxial ferroelectric PbTiO3 films - Jari Hannu; Jani Peräntie; Sergiu Mihai Stratulat; Heli Jantunen; Marina Tyunina (Journal of Advanced Dielectrics, 2016)
Ability of epitaxial perovskite oxide ferroelectric films to maintain a poled polarization state on a long-term scale is crucial for advanced devices employing such films. Here polarization relaxation with time, or aging, is experimentally studied in epitaxial capacitor heterostructures of PbTiO3 sandwiched between SrRuO3 and Pt electrodes. The relaxation obeys logarithmic time-decay for the time 102–105s after poling pulses. The decay is by factor ∼10 slower than that reported for polycrystalline films. Our experimental results show that existing models are insufficient for epitaxial films.